Intrathecal Dexmedetomidine Combined With Ropivacaine in Cesarean Section: A Prospective Randomized Double-Blind Controlled Study - Zhang, Qian; Xia, Ling-yi; Liang, Wei-dong; Rao, Ding-yu; Zhu, Ping-ping; Huang, Ke-nv; Deng, Zi-hao; Zhong, Mao-lin (Frontiers in Medicine, 2022)
Objective: This study aimed to find the best dose of dexmedetomidine in spinal anesthesia for cesarean section. Methods: 120 ASA I and II parturients undergoing elective cesarean delivery under spinal anesthesia were randomly allocated into four groups treated with intrathecal ropivacaine (12 mg) alone (Group R) or in combination with dexmedetomidine 5 μg (Group RD1), 7.5 μg (Group RD2) and 10 μg (Group RD3).Characteristics of spinal anesthesia, hemodynamic changes, adverse effects, stress reactions and neonatal outcomes were recorded in the four groups. Results: Patients in Group RD1, RD2 and RD3 had significantly longer sustained sensory and motor block time than patients in Group R. All four groups had comparable onset times of sensory and motor block. The time for the level of sensory block to lower to S1 was longer in Group RD1, Group RD2 and Group RD3 than in Group R (p < 0.001). The time to recover from motor block to a Bromage score of IV was longer in Group RD1, Group RD2 and Group RD3than in Group R( p < 0.01). The incidence of chills was significantly lower in the Group RD1, RD2 and RD3 than in the Group R (p < 0.001). There was no significant difference in the incidence of adverse effects in the four groups(p > 0.05). There was no statistically significance on fentanyl use in the four groups(p > 0.05). Phenylephrine dosing was significantly higher in Group RD2 and RD3 than in Group R (p < 0.05), and there was no significant difference in phenylephrine dosing between Group RD1 and Group R(p > 0.05). There were no statistical differences in postnatal Apgar scores (1 min, 5 min after birth) (p > 0.05). The postoperative concentrations of β-endorphin , cortisol and TNF-α in the Group RD1, RD2 and RD3 were lower than that in Group R(p＜0.05). Conclusion: Intrathecal 5µg of dexmedetomidine as an adjuvant to ropivacaine relieved intraoperative chills, did not increase intraoperative and postoperative adverse effects, did not increase the amount of intraoperative vasoconstrictor used, and prolonged the duration of maternal sensory and motor block, so this dose is appropriate for cesarean section.